PENGARUH TEKNIK RELAKSASI OTOT PROGRESIF TERHADAP PENURUNAN KADAR GULA DARAH PADA PASIEN DIABETES MELLITUS TIPE 2 DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Tati Murni Karokaro; Muhammad Riduan (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2019)
The prevalence of diabetes occuring in 2015 is 9,3% and is expected to increase annualy. Type 2 diabetes mellitus occurs because insulin resistance, which glucose fails to enter the cell, usually occurs in the age above 30 years. One of the modalitas therapy that can be done is progressive muscle relaxation. The purpose of the study was to the identify the effect of progressive muscle relaxation therapy on the decrease in blood sugar levels in patients with type 2 diabetes mellitus at hospital GRANDMED Lubuk Pakam. This research method used pre-experimental design with one group pretest-posttest. A sample size of 10 respondents selected by sampling technique of non-probability sampling type consecutive sampling. The result of paired hypothesis test of t-test sample at significance level 95%obtained p Value < Î±, that is 0,001 indicates that there is influence of progressive muscle relaxation therapy to decrease blood glucose level in type 2 diabetes mellitus patient. Conclusion obtained there is significant difference between blood glucose levels before and after progressive muscle relaxation therapy. It is sugessted that health care institutions need to implement new policies related to the application of progressive muscle relaxation therapy.